Shaping children's digital futures: The role of parenting strategies in regulating children's technology use - Yakup Yildirim; Serpil Celikten Demirel; Burcu Avcioglu (Acta Psychologica)
Purpose: This study examines the influence of Digital Parental Awareness (DPA) and parenting strategies on children's Problematic Technology Use (PTU), emphasizing behavioral and relational attitudes. Recognizing the growing role of digital parenting in guiding children's technology use, the research considers two DPA sub-dimensions: Efficient Usage (leveraging technology for growth) and Protecting from Risks (preventing exposure to harmful content). Methods: The research analyzed data from 314 parents through validated scales evaluating digital awareness, parenting attitudes, and PTU. A parallel mediation model using structural equation modeling (SEM) was employed to explore the mediatory roles of behavioral and relational attitudes in the relationships between DPA sub-dimensions and PTU. Results: Efficient Usage and Protecting from Risks significantly predicted lower PTU levels. Behavioral attitudes, such as rule-setting, mediated a substantial portion of these relationships, showing immediate tangible effects, especially within Efficient Usage. Conversely, relational attitudes (e.g., trust-building) demonstrated limited mediation effects, reflecting their influence on longer-term outcomes rather than immediate behavioral changes. Unexplored factors, including socio-cultural influences, appeared to partially account for persistent direct effects. Conclusions: The findings underscore the need for balanced parental strategies and digital literacy programs to enhance DPA, empowering parents to create healthier, safer digital environments. Future research should expand on socio-cultural contexts, peer influences, and longitudinal impacts to refine intervention frameworks.